ANALISIS DAMPAK PENDIDIKAN DAN PELATIHAN TERHADAI KINERJA DOSEN TETAP DI IBI DARMAJAYA - Sri Rahayu (Jurnal Bisnis Darmajaya, 2020)
Lecturers are human resources (HR) who have an important role for the development of a tertiary institution. In creating these human resources, education and training are the most dominant factors in improving the performance of the lecturers concerned. This study discusses the impact between education variables and training variables. The data collection in this study used a questionnaire distribution technique (to the Permanent Lecturer of IBI Darmajaya) which was tested through an instrument test and then assisted in processing it using the Statistical  Product and Service Solutions (SPSS) Application Program. The results of the study indicate that the education and training variables are strategic variables to support the lecturers' performance. This education and training variable is strategic because it has a significant positive impact on performance. The reference of this research is to improve the quality of lecturer performance, the organization must first improve the education model and lecturer training model.Keywords — Education, Training, Strategic and Performance